1954
DOI: 10.1039/jr9540000931
|View full text |Cite
|
Sign up to set email alerts
|

Paracyanogen: its formation and properties. Part I

Abstract: The brown residue, obtained by heating oxamide for several hours in a sealed tube, has been shown to be paracyanogen. The chemical and physical properties and infra-red spectra have been compared with those of paracyanogen prepared by thermal decomposition of mercuric and silver cyanides. Some suggestions are put forward with regard to its structure.IN an attempt to grow large crystals of oxamide by slow sublimation a brown residue was found in the hot section of the sublimation tube. It was suspected that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The IR spectra given by Bircumshaw et al 14 of paracyanogen prepared by different methods show some similarities and some differences to those obtained here. A broad band, centered at 1570 cm…”
mentioning
confidence: 55%
“…The IR spectra given by Bircumshaw et al 14 of paracyanogen prepared by different methods show some similarities and some differences to those obtained here. A broad band, centered at 1570 cm…”
mentioning
confidence: 55%
“…4) shows two steps [44,45]. AP on heating first loses 25% of its mass at around 300 • C, i.e., low temperature decomposition (LTD).…”
Section: Thermal Analysismentioning
confidence: 99%
“…Pendant CN groups are suggested by the band at 2220 cm −1 , while for azomethine the chains -C l N-are suggested by the intense and broad band in the range between 1650 and 28 F. Cataldo 1450 cm −1 (Peska et al 1966 ;Chen & Labes 1985) (see Fig.1). However, other authors (Birkumshaw et al 1954) proposed a ladder (polypyrazinopyrazine) structure for paracyanogen obtained by thermal decomposition reactions of inorganic salts (see Scheme 1, structure [D]). Very recent reinvestigation of the structure of paracyanogen (Jenneskens et al 1994) has substantially confirmed early spectroscopic results (Birkumshaw et al 1954), with the product showing essentially three bands : 2200 cm −1 owing to -CN groups, an intense and broad azomethine band with a maximum at " 1500 cm −1 and another broad band in the 700-800 cm −1 region (Jenneskens et al 1994).…”
Section: Recent Results Concerning Dicyanogen Polymerizationmentioning
confidence: 99%